Physical Activity Siswa SMA Negeri 3 Purwakarta di Masa Pandemi Covid-19 - Putri Dwi Renti; Febi Kurniawan; Fahrudin Fahrudin (Peneliti.net, 2021)
Abstract As written on the background in the study, the purpose of this study was to determine the physical activity of SMAN 3 Purwakarta students during the covid-19 pandemic for one week. This research is a descriptive research in the form of quantitative data, the method used in this research is a survey method using random sampling technique. Another term for random sample is one in which all individuals in the target population have an equal opportunity to choose. The population in this study were all students of class XI IPA SMAN 3 Purwakarta, totaling 160 students. Based on the results of the study, the percentage that the physical activity of SMAN 3 Purwakarta students during the Covid-19 pandemic was male students in the